Konsep Ji’alah dalam Perspektif Imam Al-Nawawi Terhadap Sistem Upah dalam Program Afiliasi Tiktok - Sholichah, Mas Amaliyatus; Mustofa, Imron; Rohmah, Elva Imeldatur (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
The In today's digital era, many people are leveraging social media platforms such as TikTok to earn additional income through TikTok affiliate programs. Consequently, the use of TikTok affiliate programs is increasingly widespread and highly sought after by the public. However, there are concerns regarding the validity of the ji'alah contract, which serves as the foundation of this program. The ji'alah contract is a legitimate transaction according to Shariah law, where rewards or percentages are given to individuals who have contributed to performing a certain task. The purpose of this research is to find solutions to this issue, with a focus on the concept of ji'alah according to Imam al-Nawawi. The research method used is a literature review with a qualitative approach, involving document analysis, secondary data, and interviews with relevant parties. The findings of this research will identify the pillars of ji'alah that are in accordance with Shariah principles and relevant in the current context of TikTok affiliate programs. The implications of this research include a better understanding of the concept of ji'alah and its application in TikTok affiliate programs, as well as recommendations to ensure the compliance of these programs with Shariah principles.